A Christian Leadership Review on Youth Self-Leadership and Self-Efficacy Relations: : A Study of Christian Leadership: Learning from Timothy and Titus - Nole, Otniel Aurelius; Balleo, Florensia Dana Carla (IAKN TORAJA, 2024)
Abstract: Youth have self-leadership in their leadership spirit. They have efficacy regarding their belief in themselves as leaders to work. If leadership indicates a role model, then Timothy and Titus were two role models who represent the position and role of youth from the perspective of the Christian faith. In this regard, the aim of this research was to analyze the relationship between self-leadership and self-efficacy in youth by learning from Timothy and Titus from a Christian leadership perspective. This research used a literature review approach as part of a qualitative method. Researchers found that self-leadership and self-efficacy in young people were related to reflecting the qualities of leaders and their leadership, as in Timothy and Titus. Charismatic leaders are those who exercise their leadership by focusing on God. Leadership means the ability to be selfless but to have an interest in implementing goodness. In principle, the effort to lead essentially contains Christian values, which include an emphasis on God's grace for humans. Keywords: Christian leadership, self-efficacy, self-leadership, youth